1996
DOI: 10.1159/000266380
|View full text |Cite
|
Sign up to set email alerts
|

Cul-de-Sac Hypernasality Test with Pattern Recognition of LPC Indices

Abstract: Acoustic differences between samples of [i], [u], and [a] uttered in nose-open and nose-obstructed condition were studied in 6 women with isolated cleft palate and pathological nasalance scores and 9 healthy women with normal nasalance scores. The speech samples were depicted by 14-component vocal tract area feature vectors obtained by linear prediction and the differences between the samples were studied with a self organized feature map. Each location on the map corresponds to a certain signal pattern, neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In the measurement of speech signals distances from the signal pattern Euclidean, weighted Euclidean, Hamming and weighted Hamming metrics were used. Differences in distances from the speech signal pattern identified in this way were a measure of deformation of human voice [6,7]. In this paper, the choice of metrics has been made taking into account that the most meaningful are those whose values show greater differences.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In the measurement of speech signals distances from the signal pattern Euclidean, weighted Euclidean, Hamming and weighted Hamming metrics were used. Differences in distances from the speech signal pattern identified in this way were a measure of deformation of human voice [6,7]. In this paper, the choice of metrics has been made taking into account that the most meaningful are those whose values show greater differences.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The Nasometer is an instrument designed to measure the degree of nasality in speech. Recently, this instrument has received increasing acceptance [10][11][12][13][14][15]. The princi ple of the Nasometer consists in a comparison of the nasal and oral components of a subjects' speech.…”
Section: Instrumentationmentioning
confidence: 99%
“…Some other studies confirm Gutzmann's [3] findings. Acoustic vocal tract area features, derived from vowels by predictive coding were exam ined with a self-organized feature map in nose open condition (NOpC) and NObC hvpernasal and normal speakers [5]. It was found that in hypemasal speakers the obstruction of the nose induced a significant change in the map location of the vowels [i] and [u].…”
Section: Introductionmentioning
confidence: 99%